Home is somewhere else : autobiography in two voices - Furst, Desider (SUNY series, the margins of literature., 1994)
An Austrian father and daughter alternate chapters to recount how in 1938 they found themselves with German passports stamped with the red J for Jewish, escaped from Vienna and made their way to London where they lived out the war as enemy aliens, and emigrated to the US in 1971. Their story is typical of many eastern Europeans of the period. No index or bibliography. Annotation copyright by Book News, Inc., Portland, OR.